East meets West: When the Islamic and Gregorian calendars coincide. Issue 4 (June 2018) - Tantisantiwong, Nongnuch; Halari, Anwar; Helliar, Christine; Power, David
Abstract: Recent research has documented that at the time of religious celebrations in Muslim countries, such as Ramadan, there is a "festival" effect in share returns. In the Gregorian calendar, December is also a time of celebration and festivities which may be associated with patterns in the behaviour of security prices. Further, the first month of the year in the Islamic calendar, Muharram, is a time of sadness and mourning for some believers, and there may be an effect when the Islamic first month of the year overlaps with the first month of the Gregorian year - January. Over a 33-year cycle, each Islamic month falls in a Gregorian month for about 5–6 consecutive years; when this happens, an Islamic (Eastern) calendar effect may interact with a Gregorian (Western) calendar effect. The current paper addresses this issue by examining the behaviour of share returns and volatility for individual companies listed in Muslim countries' stock exchanges when the two calendars coincide for: (i) religious festival effects; (ii) first-month-of-the-year effects; and (iii) the two most common effects reported in the Islamic and Gregorian calendars (Ramadan and January). The results show that the Western and Eastern effects interact more prominently in larger companies and in larger or more developed markets.